(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
The article deals with expression of concept “Soul-руўх” in Byron and Ibrayim Yusupov’s poetry, who are national poets of English and Karakalpak peoples.